Identificação de flavonóides e taninos em extrato antiviral de folhas de pitangueira (Eugenia uniflora) por espectrometria de massas de altíssima resolução (FT-ICR MS) - Oliveira, Fernanda Mirella Garcia de (2018)
The Eugenia uniflorais a species rich in a variety of tannins and flavonoids and these compounds has been reported as several biologic activities.In addition, the infusion of its leaves is widely used by the population as an aid in the treatment of dengue fever. Due to the fact that the Mayaro virus (MAYV) resembles the dengue virus (DENV), biological tests were carried out on the ethyl acetate partition of the hydroalcoholic extract of the E. uniflora leaf with the collaboration of the Institute of Microbiology Paulo de Goés -UFRJ, so that the antiviral activity of the extracts was tested and was effective against the MAYV. Two extraction methods were compared, one of them being basedon solvent extraction by successive liquid/liquid partition and the other on the extraction based on the crushing of the sheets with silica gel followed by elution with solvents. Analyses by (-)ESI-FT-ICR MSwas used to trace the chemical profile of the fractions rich in flavonoids obtained and to compare the efficiency of extraction methods.The extractive efficiency, the ease of identification of flavonoids and the qualitative determination of myricitrin were evaluated by different techniques in regard to obtaining the extracts and the analysis by FT-ICR-MS in negative mode coupled to the sources of ionization electrospray, paperspray and Leafspray. Several flavonoids could be detected in their deprotonated form in the regions of m/z400 to 600, and myricitrin (m/z463 [C21H19O12-H]-)and its chlorine adduct (m/z 499 [C21H20O12+Cl]-) showed more intense signals. Glycosides of quercetin like m/z447 -C21H19O11 and m/z,gallic acid (m/z169 -C7H5O5) and methyl gallate (m/z183 -C8H7O5), tannins precursors,have also been identified.ESI (-) was better able to analyze the chemical profile of the extracts and when associated with solvent extraction by successive liquid/liquid partition showed more intense signals for myricitrin and its derivatives while theother method of extraction showed greater selectivity in obtaining myricitrin. Although the leafspray and paperspray sources have the advantages of ease of sample preparation and simplicity of analysis, in this case they provided less intense signals for the compounds of interest and did not identify other compounds already observed by the electrospray ionization source